2022
DOI: 10.3390/foods11223725
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drought Stress on Physiological Responses and Bioactive Compounds in Chicory (Cichorium intybus L.): Opportunity for a Sustainable Agriculture

Abstract: Food production from agriculture depends on irrigation, mainly in poor rainfall zones, such as the Mediterranean region. Chicory is an important food crop component of the Mediterranean diet. Considering the increasing incidence of drought due to climate change, this study was carried out in order to investigate the effect of moderate drought stress on photosynthesis, leaf gaseous exchange, growth, and tocol and carotenoid composition of chicory under field conditions. Chicory was subjected to rainfed conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…All used vegetables have been proved to have high amounts of tocols, in the form of α and γ‐tocopherol, as reported in our previous published papers (Fratianni et al ., 2021; Delfine et al ., 2022). The formulation of the enriched pasta with 15% vegetables was made considering the initial tocol amounts of chard, being the sample with the less contents (about 14 mg/100 g of α‐tocopherol and 2.2. mg/100 g of γ‐tocopherol, expressed on dry weight).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All used vegetables have been proved to have high amounts of tocols, in the form of α and γ‐tocopherol, as reported in our previous published papers (Fratianni et al ., 2021; Delfine et al ., 2022). The formulation of the enriched pasta with 15% vegetables was made considering the initial tocol amounts of chard, being the sample with the less contents (about 14 mg/100 g of α‐tocopherol and 2.2. mg/100 g of γ‐tocopherol, expressed on dry weight).…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the content of single and total tocols of the developed pastas, expressed as mg/100 g of fresh weight (f.w.). The tocol pattern reflected that of semolina (whose main isomer is β‐tocotrienol) and of the original vegetables used for the enrichment (Fratianni et al ., 2021; Delfine et al ., 2022). The total tocol content significantly increased in the enriched pasta samples, from two to four‐folds in BP and SP, respectively ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several pieces of evidence support the positive effect of water availability on chicory yield [ 42 , 43 ]; furthermore, the reduced water availability imposes morphological changes on chicory plants, such as in the canopy structure, and this negatively affects biomass accumulation [ 15 , 16 ]. In a recent study, chicory plants submitted to the stressor of rainfed conditions showed an increase in carotenoid and tocopherol contents, suggesting thee positive effect of moderate rainfed drought stress on the plants [ 44 ].…”
Section: Introductionmentioning
confidence: 99%